Students’ Misconceptions in Solving Integer Operation Problems: Kesalahpahaman Siswa dalam Memecahkan Soal Operasi Bilangan Bulat - Mawaddah, Mira; Wardana, Mahardika Darmawan Kusuma (Indonesian Journal of Education Methods Development, 2025)
General Background: Understanding integer operations is a fundamental mathematical skill for elementary students. Specific Background: Many students continue to experience errors and misconceptions when completing integer addition and subtraction tasks. Knowledge Gap: Previous studies have discussed misconceptions broadly, but specific patterns of errors in classroom contexts remain underexplored. Aims: This study aims to identify and analyze students’ misconceptions in solving integer operation problems. Results: The findings show that students commonly misunderstand the role of zero, misapply rules for negative numbers, and rely on inconsistent informal strategies. Several error patterns consistently appear, indicating limited conceptual understanding. Novelty: This study provides detailed classifications of misconception types based on actual student work, offering clearer insight into their reasoning patterns. Implications: The results suggest the need for instructional strategies that target conceptual clarity and provide structured support for students’ understanding of integer relationships. Highlights: Misconception patterns identified Misunderstanding of zero and negative numbers Classroom-based error analysis Keywords: Integer Operations, Misconception, Elementary Students, Mathematics Learning, Error Analysis